Personalized Gamma Knife radiosurgery for cavernous sinus hemangiomas: A Chinese single-center retrospective study for 10 years of 187 patients. Issue 6 (7th July 2022) - Yang, Ruyi; Xv, Ziqiang; Zhao, Puxue; Li, Junwu; An, Quan; Huang, Shan; Wang, Xinjun
Abstract: Background: The aim of this study is to retrospectively review the effectiveness and safety of personalized Gamma Knife radiosurgery (GKRS) for cavernous sinus hemangiomas (CSHs) and to summarize experience of personalized GKRS treatment for different volume of CSHs. Methods: 187 CSHs patients who received personalized GKRS treatment in our center from January 1, 2011 to December 31, 2020 were enrolled in this study and classified into small and medium CSHs (<20 ml), large CSHs (20–40 ml) and giant CSHs (≥40 ml) according to tumor volume. The personalized GKRS treatment strategy included single GKRS and staged GKRS. Tumor shrinkage rate, clinical symptoms response, and complications after GKRS were recorded during the follow-up period. Multivariate factors influencing clinical symptoms response were analyzed after personalized GKRS treatment. Results: After a mean follow-up duration of 28 months (range 12–124 months), the tumor control rate was 100%, and the mean shrinkage rate of CSHs was 93.2% (61.3%–100%) in the last follow-up. Of the 115 patients with preexisting symptoms, 43 (37.5%) patients showed symptom disappearance, 17 (14.7%) patients demonstrated improvement, and 55 (47.8%) patients remained with no change. Previous surgical resection of CSHs ( OR = 0.025, 95% CI 0.007–0.084, P = .000) was identified to be an independent risk factor for no symptom improvement after GKRS treatment. Conclusions: Personalized GKRS is an effective and safe treatment for different volume of CSHs, which is capable of shrinking the tumor and improving symptoms with extremely low incidence of adverse effects and might be considered as the primary treatment strategy for CSHs.